2020
DOI: 10.3390/nu12113250
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Bioavailability in the Soluble and Insoluble Fibers Extracted from Opuntia ficus indica at Different Maturity Stages in Growing Rats

Abstract: Childhood and adolescence are crucial stages of life for bone health. Therefore, an adequate calcium intake and a healthy life style constitute the main strategies to prevent the risk of osteoporosis-related fractures during adulthood. It has been demonstrated that inclusion of indigestible carbohydrates in foods can help improve calcium absorption in growing stages. The objective of this study was to evaluate the effect of supplementation of soluble and insoluble fibers extracted from O. ficus indica cladodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(67 reference statements)
0
5
0
1
Order By: Relevance
“…Nevertheless, differences can be attributed to different edapho-climatic cultivar conditions and cladode age [46]. Most of the calcium contained in the mucilage is in the form of CaCO 3 , which is bioavailable [6,8,9]. As expected, due to water loss, calcium, ash, protein, and NFE contents were significantly higher in mucilage obtained from dehydrated cladodes.…”
Section: Chemical Composition Of Mucilage Extracted From Fresh and Dehydrated Cladodesmentioning
confidence: 62%
See 1 more Smart Citation
“…Nevertheless, differences can be attributed to different edapho-climatic cultivar conditions and cladode age [46]. Most of the calcium contained in the mucilage is in the form of CaCO 3 , which is bioavailable [6,8,9]. As expected, due to water loss, calcium, ash, protein, and NFE contents were significantly higher in mucilage obtained from dehydrated cladodes.…”
Section: Chemical Composition Of Mucilage Extracted From Fresh and Dehydrated Cladodesmentioning
confidence: 62%
“…Furthermore, O. ficus indica cladodes constitute an important source of minerals in the diet, mainly calcium [6]. In fact, our research group has previously demonstrated, employing models of growing and ovariectomized rats, that calcium in O. ficus indica is bioavailable [7][8][9]. The content of water in these cladodes is high (90-96 g/100 g), thus dehydration constitutes an alternative to increase the shelf life of this product, reducing transportation and storage expenses [10].…”
Section: Introductionmentioning
confidence: 99%
“…, butyrate, acetate, and propionate) by stimulating pH decline and thus increasing the solubility and transcellular absorption of mineral ions like Ca 2+ and magnesium. 84…”
Section: Resultsmentioning
confidence: 99%
“…83 When compared to rats fed HF/NaCl diet, rats given either okra mucilage or flesh, more specifically mucilage, experienced a significant increase in serum Ca, Mg, and K and a significant decrease in Na and P. This effect may be attributed to the fermented indigestible carbohydrates in okra mucilage and flesh, which can be fermented in the large intestine, thus enhancing calcium absorption by producing particular SCFA (i.e., butyrate, acetate, and propionate) by stimulating pH decline and thus increasing the solubility and transcellular absorption of mineral ions like Ca 2+ and magnesium. 84 3.8.7. Effects of okra mucilage and flesh on urinary and femur electrolytes in HF/NaCl fed rats.…”
Section: Papermentioning
confidence: 99%
“…In growing male Wistar rats, cladodes at the late maturity stage were reported to contribute to bone formation (Hernandez‐Becerra et al, 2020); in addition, soluble fibers obtained from cladodes at late and early stages of maturity showed better bone properties (calcium content, resistance to fracture, and microarchitecture) when compared to control and rats fed with cladodes' insoluble fibers (Mendoza‐Ávila et al, 2020). Calcium from cladodes' (at late maturity stage) soluble fibers was reported by Quintero‐García et al (2020) to be bioavailable and to help in the improvement of microstructural, biomechanical, densitometric, and physical bone properties in ovariectomized rats.…”
Section: Biological Activitiesmentioning
confidence: 99%